1240. Persistence of Circulating Antibody Through 12 Months Following Vaccination With a 20-Valent Pneumococcal Conjugate Vaccine in Adults 60–64 Years of Age. (31st December 2020) - Hurley, Donald; Griffin, Carl; Young Jr., Mariano; Scott, Daniel; Pride, Michael W; Scully, Ingrid L; Ginis, John; Peng, Yahong; Jansen, Kathrin U; Gruber, William C; Watson, Wendy
Abstract: Background: While widespread use of pneumococcal conjugate vaccines (PCVs) has reduced disease burden, expanding serotype coverage remains an unmet need in disease prevention. The 20-valent PCV (PCV20) contains capsular polysaccharide conjugates from serotypes included in the 13-valent PCV (PCV13; Prevnar 13®) as well as 7 additional serotypes. In a phase 2 study of PCV20 in adults 60–64 years of age, robust immune responses were observed at 1 month after vaccination; antibody persistence up to 12 months after vaccination from that study is described herein. Methods: In this randomized, active-controlled, double-blind study (ClinicalTrials.gov NCT03313037), adults aged 60–64 years received a single PCV20 dose followed 1 month later by saline placebo or PCV13 followed 1 month later by 23-valent pneumococcal polysaccharide vaccine (PPSV23), which provided benchmarks for all PCV20 serotypes. Immunogenicity was assessed at baseline and at 1 and 12 months after vaccination as serotype-specific opsonophagocytic activity (OPA) geometric mean titers (GMTs) and immunoglobulin G (IgG) geometric mean concentrations (GMCs). OPA and IgG geometric mean fold rises (GMFRs) from baseline to 12 months after vaccination were assessed. Results: In the PCV20 group, OPA GMTs (n=185–200 at Month 12) for all PCV20 serotypes increased substantially from baseline to 1 month after vaccination and then declined by Month 12 but remained elevated above baseline. OPA GMFRs from baseline to Month 12 after PCV20 vaccination were 1.9–15.0 for the serotypes in common with PCV13 and 5.6–15.6 for the 7 additional serotypes. Similar results were observed for IgG concentrations, with GMFRs of 2.4–9.4 for the PCV13 serotypes and 3.0–15.5 for the 7 additional serotypes. At Month 12, 11 months after PPSV23 vaccination (n=162–195), OPA GMFRs were 5.3–11.5 for the 7 additional serotypes; IgG GMFRs were 5.0–10.4. Benchmarking to PCV13 serotypes in the control group was not appropriate as these subjects received both PCV13 and PPSV23, which overlap in polysaccharide composition for 12 serotypes. Conclusion: Immune responses induced by PCV20 persisted at 12 months after vaccination in adults 60–64 years of age, further supporting the potential of PCV20 to expand serotype protection against adult pneumococcal disease. Disclosures: Mariano Young Jr., MD, Pfizer Inc (Employee, Shareholder) Daniel Scott, MD, Pfizer (Employee, Shareholder) Michael W. Pride, PhD, Pfizer (Employee, Shareholder) Ingrid L. Scully, PhD, Pfizer Inc (Employee, Shareholder) John Ginis, BS, Pfizer Inc (Employee, Shareholder) Yahong Peng, PhD, Pfizer (Employee, Shareholder) Kathrin U. Jansen, PhD, Pfizer (Employee, Shareholder) William C. Gruber, MD, Pfizer (Employee, Shareholder) Wendy Watson, MD, Pfizer (Employee, Shareholder)